Early polls make sense in a worsening pandemic - EUGENE, Tan K. B. (Institutional Knowledge at Singapore Management University, 2020)
In a commentary, SMU Associate Professor of Law Eugene Tan opined there is no good time for a general election amid the global pandemic, and it is a judgment call on when to hold Singapore's 13th general election, which must take place by April next year at the latest. He believes early polls make sense in a worsening pandemic if the Government ensures that even as candidates campaign, there is no let-up in the fight against the outbreak.